2011
DOI: 10.1007/s10936-011-9189-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Non-Lexical Influence on Children’s Auditory Repetition of Familiar Words

Abstract: This paper examines evidence for a nonlexical influence on children's repetition of real words. We investigate the extent to which two computational models of auditory repetition can simulate the performance of 68 children aged between 5 and 11 years-old when they are attempting to repeat familiar words. Both computational accounts were derived from Foygel and Dell's (J Mem Lang 43:182-216, 2000) semantic-phonological model of picture-naming. Results showed that a dual-route model in which a lexical and a nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Orélis-Ribeiro et al [27], fulfilling the rigorous Koch postulates, concluded that the Exophiala cancerae species is the causative agent of LCD. His results support that the fungal agent is pathogenic and upheld the hypothesis of Boeger et al [12,15] that associated this fungus with LCD and the mass die offs of crabs.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Orélis-Ribeiro et al [27], fulfilling the rigorous Koch postulates, concluded that the Exophiala cancerae species is the causative agent of LCD. His results support that the fungal agent is pathogenic and upheld the hypothesis of Boeger et al [12,15] that associated this fungus with LCD and the mass die offs of crabs.…”
Section: Discussionsupporting
confidence: 65%
“…Interestingly, while the interviewees could not name the disease that was infecting the crabs in the region, all of them could identify the major clinical symptoms of LCD. This inability to correctly name the disease is almost certainly due to the fact that it was only recognized and named by Boeger et al [15] (in reference to the lethargy demonstrated by infected crustaceans). These authors provided robust evidence suggesting that LCD is caused by an anamorph fungus and phylogenetic analyses have confirmed the diagnosis of the LCD fungus as an ascomycete (fungus of the phylum Ascomycota), and they suggest a close relationship with members of the subphylum Pezizomycotina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variability, however, reflects the nature of the verbal stimulus, rather than brain damage. The nonlexical route is recruited when the item to be repeated is not part of the person's lexicon (as in learning a new language, or when the word is simply not known), and as such cannot be looked up in the production system (See also Budd, Hanley, & Nozari, 2012, for a report on the differential use of lexical-route and dual-route models innormally-developing children of different age groups).…”
Section: Discussionmentioning
confidence: 99%
“…The S and P parameter strengths were estimated by fitting Foygel and Dell's model to the pattern of errors that each child made when naming the pictures (See Methods for details of model fitting). The success of this technique in estimating the strength of semantic and phonological processing in children's production system, and in detecting increases in the strength of the S and P parameters as children get older, has been previously established (Budd, Hanley & Griffiths, 2011;Budd, Hanley & Nozari, 2012). We then tested the model's prediction that the strength of S, but not P, should be predictive of the detection of semantic errors in the moving animals task.…”
mentioning
confidence: 99%